Cucumber Juice Therapy as a Non-Pharmacological Intervention for Hypertension Patients: A Case Study in South Konja, Majene Regency - Nurwahita; Moh. Wafri Matorang; Helmi Juwita; Muhammad Qasim (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Hypertension is one of the most common non-communicable diseases and a major risk factor for cardiovascular morbidity and mortality. Non-pharmacological interventions, such as herbal remedies, are increasingly considered as alternatives to medication, especially among the elderly. This study aimed to determine the effect of cucumber juice on lowering blood pressure in hypertensive patients. The study used a quantitative descriptive method with a pre-experimental one-group pretest-posttest design. It was conducted in Dusun Konja Selatan, Pamboborang Village, Majene Regency, involving three respondents who were not taking antihypertensive drugs. Each participant consumed 200 ml of cucumber juice once daily for three non-consecutive days. Blood pressure was measured before and 30–60 minutes after consumption. Results showed a consistent reduction in systolic and diastolic blood pressure across all respondents, with decreases ranging from 10 to 40 mmHg. Respondents also reported feeling more relaxed and experiencing improved urination. These findings support the potential of cucumber juice as a complementary therapy for hypertension due to its high potassium, magnesium, and water content, which promote diuretic and vasodilatory effects. In conclusion, cucumber juice may be a practical, safe, and accessible non-pharmacological option for managing hypertension, particularly in community health settings.